Assessment of Some Biochemical Markers (Protein Levels, Hepatic Enzymes, Calcium, and Iron) Status in Patients of Diabetic Nephropathy in Thi-Qar/ Iraq - Hameed, ‎ Ayat Rasheed; Salih, Rasha (University of Thi-Qar Journal of Science, 2025)
Diabetic nephropathy is a kidney disease that develops as a complication of diabetes, and it is issociated with renal impairment with increasing age. Renal impairment among diabetic individuals can be detected using serum markers of glomerular filtration rate and microalbuminuria. This study was carried out at AL-Hussein Hospital and Consulting Laboratories .The study period extended from October 2024 to January 2025. aiming to assess the biochemical changes in kidney failure patients with and without diabetes. Based on the results, it was noted that diabetic patients had higher levels of total protein and lower levels of albumin compared to the healthy control group. Additionally, patients with diabetic nephropathy had elevated levels of liver enzymes (ALT, AST, and ALP), C-reactive protein (CRP) ,and calcium. A noticeable lower iron levels were observed in both diabetic and diabetic nephropathy groups compared to the healthy control group.